Circulating anti-galectin-1 antibodies are associated with the severity of ocular disease in autoimmune and infectious uveitis - Romero, Marta D. (2006)
Galectin (Gal)-1, an endogenous lectin found at sites of immune privilege, plays a critical role in the regulation of the immune response. Therapeutic administration of Gal-1 or its genetic delivery suppresses chronic inflammation in experimental models of autoimmunity. The purpose of this work was to investigate the occurrence of circulating anti-Gal-1 antibodies in patients with autoimmune and infectious uveitis as potential determinant factors of disease progression.